1995
DOI: 10.1177/43.2.7529786
|View full text |Cite
|
Sign up to set email alerts
|

Odontoblast processes in dentin revealed by fluorescent Di-I.

Abstract: There has been controversy about the length and structure of the odontoblast process within dentin since the earliest histologic studies of teeth. Our objective was to use the fluorescent carbocyanine dye Di-I combined with a new gelatin embedment procedure and confocal microscopy to determine the structure and extent of odontoblast processes in developing and mature rat teeth, injured rat molars, reparative dentin, and adult monkey teeth. We found that odontoblast processes do not extend into outer dentin or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
4
27
0
2
Order By: Relevance
“…These observations are consistent with previous studies where an increased density, and a notable development of afferent peptidergic innervations, was recorded in early stages of pulp response [Byers and Sugaya, 1995;Rodd and Boissonade, 2002]. Further, numerous studies on dental pulp innervation have shown that sensory nerve fibres are dynamic elements which react to injury and inflammation by sprouting and altered cytochemical phenotype [Byers and Närhi, 1999].…”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with previous studies where an increased density, and a notable development of afferent peptidergic innervations, was recorded in early stages of pulp response [Byers and Sugaya, 1995;Rodd and Boissonade, 2002]. Further, numerous studies on dental pulp innervation have shown that sensory nerve fibres are dynamic elements which react to injury and inflammation by sprouting and altered cytochemical phenotype [Byers and Närhi, 1999].…”
Section: Discussionsupporting
confidence: 92%
“…Interglobular dentine is present only in the crown and not in the root, whereas the granular layer of Tomes is present only in root dentine (Avery 1991;Piesco 1994). The branching pattern of the dentinal tubules is different in the crown and the root (Byers and Sugaya 1995). These characteristics of coronal and radicular dentine are confirmed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The structure of dentinal tubules has been investigated using various methods such as light microscopy including the use of microradiographs, scanning and transmission electron microscopy, and atomic force microscopy. Confocal microscopy has been also applied for the observation of dentine (Watson 1989(Watson ,1990Byers and Sugaya 1995;Kabasawa et al 1995), however, the effective staining method for the dentinal tubules is limited. For the staining of mineralized tissues, fluorescent dyes such as alizarin red, calcein, and tetracycline have been used for vital staining.…”
Section: Introductionmentioning
confidence: 99%
“…2), with much fewer nerve endings in peripheral pulp or dentin of the roots. The gradients are present from the earliest periods in development of the dental sensory innervation of crown, and they correspond to gradients in pulpal secretion of growth factors such as nerve growth factor (Byers et al, , 1992a or glial-derived neurotrophic factor (de Vincente, 2002) and to odontoblast morphologic phenotypes (Byers and Sugaya, 1995;Ohshima et al, 2001). During maturation and aging, the neural patterns are maintained where primary dentin and odontoblasts survive, with a continued focus on the pulp/ dentin complex beneath enamel Byers, 1996).…”
Section: Normal Innervation Of Teethmentioning
confidence: 99%
“…2). The pulp cells are varied by region within the tooth, and very different cytochemistry and cell structure have been noted for coronal odontoblasts compared to radicular odontoblasts, subodontoblastic fibroblasts, undifferentiated mesenchymal cells, resident immunocompetent cells, vascular endothelium, vascular pericytes, and the supportive cells for the nerve fibers Byers and Sugaya, 1995;Fouad, 2002;Maeda et al, 1994;Ohshima et al, 2001;Okiji, 2002;Suda and Ikeda, 2002). Thus, the possible cellular interactions between the varieties of dental nerve fiber and the local cells are vast in normal teeth, and are amplified after injury by invading inflammatory and immune cells, and by infection (Inoue and Shimono, 1992).…”
Section: Normal Innervation Of Teethmentioning
confidence: 99%